Impoverishment As A Recovery Effort For Corruptors In Indonesia - Berlin Yolanda; Margo Hadi Putra (Corruptio, 2022)
Corruption is one of the symptoms that we often encounter in Indonesia. The difficulty of knowing the wealth of corruption remains complex and the weakness of law enforcement in Indonesia is one of the causes of the high level of corruption in Indonesia. Because until now, there is still a lack of judges' decisions that are deterrent to corruptors, while corruption is increasingly rampant among state officials in the legislature, executive, and judiciary, especially among law enforcement officials themselves. The type of data used by the author in this paper is normative juridical, where this research examines the legal norms contained in the law and the norms that exist in society. It can be concluded that the prevention and eradication of corruption are not enough to rely on the Corruption Eradication Act but must continue to be promoted until the corruptors are powerless and deterred. One of the preventions of criminal acts of corruption is "Corruption Impoverishment." Even though the case is still a bit of impoverishment, it should be appreciated because it provides a deterrent effect for the corruptors. The loss of property can be an unpleasant result which is one of the essential elements of prosecution. As a result of this kind of treatment, life can change if, at first, the perpetrator can live comfortably with their wealth. After being convicted, the perpetrators can fall into poverty.